Structural Reflection: Race and Class in James Baldwin’s “Sonny’s Blues” (Mindscape: A Journal of English & Cultural Studies, 2023)
This research paper explores that the African American repression against the Afro- American community in American society takes place primarily due to two factors: race and class. Behind the story of the dejected position of the Black community, there is not only a single reason but rather multiple factors that are intertwined. Basically, Baldwin’s story "Sonny’s Blues" represents that race and class seem to be contributing aspects to their disregarded presence in society. In addition, most people believe that Afro-Americans are treated as others simply due to racism in the white-dominated American society. However, using two theories: Marxist classism and African American theories, analyzing the story Sonny’s Blues, this paper aims to show how both class and race simultaneously become the basic foundation of oppression against the Afro- American community. Actually, for how long and how deeply Afro-Americans have been subjugated in American society as a consequence of their race and economic class. It means the story reveals both economic class and race would be responsible for their wretched status in the White Mainstream American society.